2012
DOI: 10.1139/y2012-096
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of dexrazoxane against acute ischaemia/reperfusion injury of rat hearts

Abstract: Dexrazoxane (DEX), an inhibitor of topoisomerase II and intracellular iron chelator, is believed to reduce the formation of reactive oxygen species (ROS) and protects the heart from the toxicity of anthracycline antineoplastics. As ROS also play a role in the pathogenesis of cardiac ischaemia/reperfusion (I/R) injury, the aim was to find out whether DEX can improve cardiac ischaemic tolerance. DEX in a dose of 50, 150, or 450 mg·(kg body mass)(-1) was administered intravenously to rats 60 min before ischaemia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…This model lacks the important local and systemic effects of I/R, caused mainly by the inflammatory and coagulatory cascades in vivo. The concept as well as our data is further supported by a study that compared in vivo and ex vivo rat models to test the effects of Dex during myocardial infarction [43]. This study showed effective reduction in infarct size of hearts treated with 150 mg/kg Dex ex vivo but not in vivo.…”
Section: Discussionsupporting
confidence: 72%
“…This model lacks the important local and systemic effects of I/R, caused mainly by the inflammatory and coagulatory cascades in vivo. The concept as well as our data is further supported by a study that compared in vivo and ex vivo rat models to test the effects of Dex during myocardial infarction [43]. This study showed effective reduction in infarct size of hearts treated with 150 mg/kg Dex ex vivo but not in vivo.…”
Section: Discussionsupporting
confidence: 72%
“…These results are consistent with the evidence that DXZ, when administered during ischemia, did not confer cardioprotection in a porcine I/R model, 24 whereas its initiation before ischemia has been shown to reduce the infarct size. 19 , 22 , 23 Deferasirox was developed to treat patients with iron overload caused by repeated transfusions. 27 Iron overload is referred to as hemochromatosis under these conditions, in which iron likely accumulates in multiple organs, including the liver and heart, resulting in cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment before ischemia with dexrazoxane, an iron chelator against Fe 3+ approved for suppressing doxorubicin cardiotoxicity, reduces the infarct size in rodent models of I/R. 22 , 23 However, treatment with dexrazoxane after the onset of ischemia, which is applicable for clinical AMI treatment, does not effectively reduce the infarct size in a porcine model of I/R. 24 This may be because of the need for dexrazoxane to be metabolized to ADR‐925 for full iron‐chelating activity after its administration.…”
mentioning
confidence: 99%
“…The mechanism of arrhythmia induced by iron overload was attributed to the following mechanisms in PD patients: (a) excessive intracellular iron interferes with electrical function of the heart, 17,18 (b) catalyze the generation of free radicals 17,19 and (c) cause selective dysfunction of Naþ channels. 15,17 Furthermore, iron overload is associated with increases in myocardial apoptosis and the development of fibrosis.…”
Section: Discussionmentioning
confidence: 99%